Pengaruh Model Karakteristik Pekerjaan Terhadap Komitmen Organisasi Karyawan - Priani, Amidya; Mukaram, Mukaram (Jurnal Riset Bisnis dan Investasi, 2016)
Organizational commitment is the individual variable that has important role in achieving organization goals. The organizational commitment will determine the employee's interest in the company that will eventually decide to stay or leaves the company. One way to increase employees' organizational commitment is to pay attention to the job characteristics. This research aims to determine how big the influence of job characteristics model to the employees of the organization's commitment technicians PT Telkom Akses Bandung. The measurement the level of job characteristics model using dimensions of skill variety, task identity, task significance, autonomy and job feedback. While the measurement of organizational commitment of employees using the dimension affective commitment, continuance commitment, and normative commitment. This research uses quantitative methods and involved 177 respondents drawn from three units of the division/unit of work. Based on the research results, the level of job characteristics model in the category"high" because it has the mean of 4.14. So even on the level of organizational commitment of employees in the category "high" because it has the mean of 3.75. The results of this research indicate that the job characteristics model can contribute to the organizational commitment of employees (R²) of 16.8%.